ANALISIS KUALITAS BAKTERIOLOGIS AIR MINUM DI RESTORAN WILAYAH KERJA PUSKESMAS BERINGIN KOTA BENGKULU - Romadhona, Mufti; yusmidiarti, yusmidiart (JURNAL MEDIA KESEHATAN, 2015)
Water is an absolute necessity for human life and other living things. But water alsoacts a medium of transmission of the disease, therefore treated water before it is consumedbeforehand to eliminate or decrease levels contaminated material to the safe levels. Many diseasaeare caused by consuming water that contain bacteria, especially bacteria Escherichia coli diarrheaexamples. The insidence of diarrhea in Indonesia population is estimated at 40-50 % per year,which occurs at age 70-80 % among toddlers. In 2012 the incidence of diarrhea in Bengkulu cityof 14.023 cases, while working in the region health center Beringin Raya Bengkulu City. Thepurpose of researchis to determine the number of Escherichia Coli in the reustaurant and themanner of presentation of drinking water as well as the source of drinking water used in therestaurant in work areaas healt center Beringin Raya Bengkulu City. The type of research methodresearch study using qualitative analtytic research with descriptive approach. Sampeles in thisstudy were 17 restaurant, analysis used univariate analisys and its tables are presented in the tableoutcome variables. The obtained test result conducted on the frequency distribution ofbacteriological quality of drinking water at restaurant in region of healt centers Beringin rayaBengkulu City based on the number of escherichia Coli is 58,82 % not eligible, 100 % how thepresentationof cups and drinking water using plastic bag, and 88,23 % drinking water sourcesusing water DAMIU. Advice to the relevan institutions to periodically conduct a review of thequality of drinking water and restaurant for releated institution recommended in order to conductthe same study thatbacteriological quality of drinking water by examinung different types ofcoliform and used more methods and meticulous advanced. In addition to further researchesconducted a study toexamine the salmonella found in drinking water.